Hormone replacement therapy attenuates hearing loss: Mechanisms involving estrogen and the IGF‐1 pathway. Issue 3 (7th March 2019) - Williamson, Tanika T.; Ding, Bo; Zhu, Xiaoxia; Frisina, Robert D.
Abstract: Estradiol (E) is a multitasking hormone that plays a prominent role in the reproductive system, and also contributes to physiological and growth mechanisms throughout the body. Frisina and colleagues have previously demonstrated the beneficial effects of this hormone, with E‐treated subjects maintaining low auditory brainstem response (ABR) thresholds relative to control subjects ( Proceedings of the National Academy of Sciences of the United States of America, 2006;103:14246; Hearing Research, 2009;252:29). In the present study, we evaluated the functionality of the peripheral and central auditory systems in female CBA/CaJ middle‐aged mice during and after long‐term hormone replacement therapy (HRT) via electrophysiological and molecular techniques. Surprisingly, there are very few investigations about the side effects of HRT in the auditory system after it has been discontinued. Our results show that the long‐term effects of HRT are permanent on ABR thresholds and ABR gap‐in‐noise (GIN) amplitude levels. E‐treated animals had lower thresholds and higher amplitude values compared to other hormone treatment subject groups. Interestingly, progesterone (P)‐treated animals had ABR thresholds that increased but amplitude levels that remained relatively the same throughout treatment. These results were consistent with qPCR experiments that displayed high levels of IGF‐1R in the stria vascularis (SV) of both E and P animal groups compared to combination treatment (E + P) animals. IGF‐1R plays a vital role in mediating anti‐apoptotic responses via the PI3K/AKT pathway. Overall, our findings gain insights into the neuro‐protective properties of E hormone treatments as well as expand the scientific knowledge base to help women decide whether HRT is the right choice for them.